The effects of replacing soybean meal with dried distillers grains with solubles in a growing Boer goat diet - Hanson, Jessica M.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
The objective was to determine what the impact of replacing soybean meal (SBM) with dried distillers grains with solubles (DDGS) has in a growing Boer goat diet, specifically on ADG, ADFI, G:F, and carcass traits. Information on goat nutrition is limited while the population continues to increase. Forty-eight growing Boer goats, at approximately 70 days of age, were divided into pens of three to determine the impact of feeding varying levels of dried distillers grains with solubles (DDGS) at the expense of soybean meal (SBM). There were four pens per treatment and four treatments. The treatments consisted of 1) 0% SBM replaced with DDGS, 2) 33% SBM replaced with DDGS, 3) 66% SBM replaced with DDGS, and 4) 100% SBM replaced with DDGS. The goats who had SBM replaced with DDGS were on a step-up diet for 14 days prior to the experiment to prevent ruminal upsets. The goats were weighed at -1 d and 0 d. After the start of the experiment, the goats and feeders were weighed weekly for the calculation of ADFI, ADG, and G:F. Goats were slaughtered on d 47 of the experiment with measurements collected of carcass weight, carcass yield, loin eye area and depth, backfat, and body wall thickness. Data analysis was run through GLIMMIX procedure in SAS. There was no difference in ADFI and carcass traits between the different treatments (P > 0.05). However, there was a linear improvement in G:F and ADG (P < 0.05) in goats fed increasing levels of DDGS. Overall, replacing SBM with DDGS has no significant reduction on the growth performance and carcass traits in a growing Boer goat diet, so it is possible to efficiently replace SBM with DDGS.
Keywords: Spring 2018